Analysis of Flood Flow of Ketibung Catchment Area Using HSS Nakayasu, Limantara and Snyder Methods - T A Saputra; Aprizal Aprizal; A Nurhasanah (International Conference on Engineering and Technology Development (ICETD), 2017)
Ketibung catchement area administratively located at Southern Lampung and Eastern Lampung districts. Ketibung river upstream is Ketibung dam that administratively located at Talang Baru village Sidomulyo districts Eastern Lampung district. Ketibung river has a variatif wide from upstream to downstream, river’s wides at the upstream approximately ± 8,5 m, wides at the middle stream approximately ± 6,8 m and at the downstream approximately ± 7,2 m, with the catchement area extensive approximately 315 km2. At these areas hidrology data are not avaliable, to decrease unit hidrograf, synthetic hidrograf unit is made according to physical characteristic of Ketibung catchement area. Using HSS Nakayasu, Limantara and Snyder methods that will be used as flow at river infrastructures planning for the flood management. From these three methods, for the biggest design flood is using Snyder method (Q25 : 653,72 m³/second), for Limantara Method (Q25:416,45 m³/second) and Nakayasu ( Q25 : 519,40 m³/second). For HSS Limantara, the top time is happened at (TP:4,91) with top flow (Qp:7,813 m³/second), while HSS Nakayasu has the same top time at (TP:4,91) with top flow (Qp:11,5 m³/second) and HSS Snyder top time happened at (Tp;5,39) with top flow (Qp:10,80 m³/second)